2014
DOI: 10.1111/hdi.12246
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous calf hematoma in a patient with diabetic nephropathy receiving maintenance hemodialysis: A case report and review of the literature

Abstract: We report the outcome of a 52-year-old patient with diabetic nephropathy and receiving maintenance hemodialysis (HD) using low molecular weight heparin (LMWH) as an anticoagulant for 2 years. He presented right lower limb pain accompanied with difficulty in walking for 2 months, and had no history of bleeding tendency or trauma. Physical examination revealed marked swelling and tenderness on his right lower limb. By ultrasound and magnetic resonance imaging (MRI) diagnoses, the calf hematoma was diagnosed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Shaw et al (2005) reported one case of small-bowel hematoma in a child who received therapeutic doses of LMWH because of deep venous thrombosis. Approximately 85% of spontaneous intestinal intramural hematomas in patients with anticoagulant therapy occur in the small bowel (Xiao et al, 2015); however, the incidence of spontaneous hematoma is extremely rare in the colon. Thus, we herein present a novel case of spontaneous intramural hematoma of the colon associated with subcutaneous LMWH therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al (2005) reported one case of small-bowel hematoma in a child who received therapeutic doses of LMWH because of deep venous thrombosis. Approximately 85% of spontaneous intestinal intramural hematomas in patients with anticoagulant therapy occur in the small bowel (Xiao et al, 2015); however, the incidence of spontaneous hematoma is extremely rare in the colon. Thus, we herein present a novel case of spontaneous intramural hematoma of the colon associated with subcutaneous LMWH therapy.…”
Section: Discussionmentioning
confidence: 99%